Fuzzy fixed points of generalized F-2-Geraghty type fuzzy mappings and complementary results - Abbas, Mujahid; Ali, Basit; Rizzo, Ornella; Vetro, Calogero (Nonlinear Analysis: Modelling and Control, 2016)
The aim of this paper is to introduce generalized F2-Geraghty type fuzzy mappings on a metric space for establishing the existence of fuzzy fixed points of such mappings. As an application of our result, we obtain the existence of common fuzzy fixed point for a generalized F2-Geraghty type fuzzy hybrid pair. These results unify, generalize and complement various known comparable results in the literature. An example and an application to theoretical computer science are presented to support the theory proved herein. Also, to suggest further research on fuzzy mappings, a Feng–Liu type theorem is proved.
Keywords: fuzzy fixed point; fuzzy mapping; sorting algorithm